2011
DOI: 10.1111/j.1464-410x.2011.10174.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in prostate‐specific antigen levels: a large cross‐sectional study of men in the UK

Abstract: • The proportion of participants who would be considered clinically at risk according to their PSA or blood pressure measurement, by month, was also assessed.• The strength of associations between time of year and blood pressure were used to reinforce conclusions from the PSA models. RESULTS• There was no relationship between time of year and PSA levels ( P = 0.11) or between climate and PSA levels ( P = 0.42).• No difference was found in the prevalence of clinically raised PSA content by month ( P = 0.50).• T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Some evidence exists for seasonal variation in PSA [46]; however, a study using ProtecT data showed no variation in PSA due to time of year or amount of sunlight per day [47] and thus time of year should not have affected these results. As not all men were biopsied, the calculated specificities and sensitivities are likely overestimates as there were likely to be men with undiagnosed prostate cancer (Box 2).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence exists for seasonal variation in PSA [46]; however, a study using ProtecT data showed no variation in PSA due to time of year or amount of sunlight per day [47] and thus time of year should not have affected these results. As not all men were biopsied, the calculated specificities and sensitivities are likely overestimates as there were likely to be men with undiagnosed prostate cancer (Box 2).…”
Section: Discussionmentioning
confidence: 99%
“…Although this method is commonly used with time series data, it can also be applied to cross-sectional survey data (Barnett and Dobson, 2010;Down et al, 2011). Inclusion of lifestyle and environmental variables including day length in multivariable models can also demonstrate whether seasonal change in depressive symptoms tracks change in day length and/or temperature, independently of confounders.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Britain based on a huge number of data claimed that there was no pattern in PSA levels by time of year, air temperature or levels of sunlight in their cohort (13).…”
Section: Discussionmentioning
confidence: 99%